Pengaruh Social Media Marketing dan Inovasi Produk terhadap Minat Beli Ulang Kopi Bubuk Instan Nescafe di Kota Bandung - Nanda, Yulia; Nurtjahjadi, Edi (Universitas Batanghari, 2024)
This research aims to analyse the impact of social media marketing and product innovation on the likelihood of repurchasing Nescafe instant coffee powder products in the city of Bandung. This research instrument has undergone rigorous testing to ensure its validity and reliability, including assessments of classical assumptions and multiple regression analysis. This instrument served as a data collection tool for respondents aged 17 years and older residing in the city of Bandung who have made a purchase of the Nescafe instant ground coffee product at least once, which is the subject of evaluation in this research. The research includes a total of 120 respondents. The data instruments are tested using the SPSS version 26 software tools, which is an analytical tool. The research findings indicate that Social Media Marketing and product innovation have a favourable and substantial impact on concurrent repurchase interest. What sets this research apart from prior studies is its focus on partial testing and the determination of the research locus specifically in the city of Bandung. The research aims to provide valuable insights for managers responsible for evaluating things, enabling them to develop effective plans or programmes